Prevalence of and Associations With Distress and Professional Burnout Among Otolaryngologists: Part II, Attending Physicians. (29th September 2020) - Carlson, Matthew L.; Larson, David P.; O'Brien, Erin K.; Lohse, Christine M.; Kircher, Matthew L.; Gurgel, Richard K.; Hunter, Jacob B.; Micco, Alan G.; Nogan, Stephen J.; O'Connell, Brendan P.; Rangarajan, Sanjeet V.; Rivas, Alejandro; et al.
Abstract : Objective: To ascertain the prevalence of and associations with distress and professional burnout among academic otolaryngology attending physicians. Study Design: Cross‐sectional survey. Setting: Twelve US academic otolaryngology programs. Methods: A questionnaire was administered that encompassed sociodemographic and professional features, the Expanded Physician Well‐being Index for distress, the 2‐item Maslach Burnout Inventory for professional burnout, the Patient Health Questionnaire–2 screen for major depressive disorder, and the Generalized Anxiety Disorder–2 screen for generalized anxiety disorder. Results: The survey response rate was 56% and included 186 attending physicians. The average respondent age was 47 years; 72% were men; 93% were married or partnered; and 86% had children. Distress was present in 40%, professional burnout in 26%, positive depression screening in 8%, and positive anxiety screening in 11%. In a univariable setting, age, hours worked in a typical week, nights on call in a typical week, and years of practice were significantly associated with distress, although in a multivariable setting, only hours worked in a typical week remained significantly associated with a positive Expanded Physician Well‐being Index screen (odds ratio for each 10‐hour increase, 2.61; 95% CI, 1.73‐3.93; P <. 001). In a univariable setting, hours worked in a typical week was significantly associated with a positive Maslach Burnout Inventory screen. Conclusion: Distress or professional burnout occurs in more than a quarter of academic otolaryngology attending physicians, whereas the prevalence of depression or anxiety is approximately 10%. The number of hours worked per week had the strongest association with distress and burnout. These findings may be used to develop and implement programs to promote physician well‐being and mitigate professional burnout.